Bernard Huet « A. Rossi ou l’exaltation de la raison » - Julien Correia (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This text by Bernard Huet (1932-2001) was published in Italian and English in 1984 in a book presenting recent projects by the Milanese architect Aldo Rossi (1931-1997). The article remains very little known, it has never been published in French, which is the original language in which it was prepared. The discovery of Bernard Huet’s original typewriting at the Centre d’archives d’architecture du XXe siècle de la Cité de l’architecture et du patrimoine in Paris encouraged us to disseminate it. The author presents Aldo Rossi’s theoretical work in a very synthetic way. It defines three moments chronologically bounded by major writings by the architects from the late 1950s to the mid-1980s. We can thus rediscover Rossi’s ideas according to the Architecture of the City, the Architecture of Reason, and the Architecture of Memory. Beyond this synthesis, the article is based on fundamental articles by Rossi for which we have taken care to complete the footnotes. Bernard Huet helps us to understand Aldo Rossi, his texts, their principles, and invites us to think about the « exaltation of reason ».